If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + -3x) = (-4x + 7) (1 * 3 + -3x * 3) = (-4x + 7) (3 + -9x) = (-4x + 7) Reorder the terms: 3 + -9x = (7 + -4x) Remove parenthesis around (7 + -4x) 3 + -9x = 7 + -4x Solving 3 + -9x = 7 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 3 + -9x + 4x = 7 + -4x + 4x Combine like terms: -9x + 4x = -5x 3 + -5x = 7 + -4x + 4x Combine like terms: -4x + 4x = 0 3 + -5x = 7 + 0 3 + -5x = 7 Add '-3' to each side of the equation. 3 + -3 + -5x = 7 + -3 Combine like terms: 3 + -3 = 0 0 + -5x = 7 + -3 -5x = 7 + -3 Combine like terms: 7 + -3 = 4 -5x = 4 Divide each side by '-5'. x = -0.8 Simplifying x = -0.8
| Z-29=3.1 | | 4k-27=-2k-9 | | 12u^2-28u-24= | | 4k-27=-2-9 | | W-13=34 | | 1n=9999999999999 | | 11(4k+6)=198 | | 3-4x+8x=20+3x | | T+5=16 | | 2(v-3)-5v=-3(v+3) | | Y-5=16 | | 8a^2+34a-9=0 | | 5.0625-x+3=0 | | (10x)(10x)+7-12=0 | | n^2+16n+64= | | n^2-9n+20= | | 34+54=11x+13 | | n^2+8n+12= | | graphy=2x-3 | | 2+-4= | | 7(3x+5y)= | | 15+3y=21 | | 2h+5=4h-9 | | 20x-10/5 | | x/-3=-6-(-4) | | 2x(2x/7)=(x/2)+(17/2) | | 3=-6(-4) | | 3(v+2)-v=2(v-1)+5 | | 4u=48 | | 3(w+2)+w=4(w-1)+10 | | (7x-5)(3x+3)= | | 77=11m |